2023
DOI: 10.1007/s11255-023-03549-6
|View full text |Cite
|
Sign up to set email alerts
|

Trends in mortality and comorbidities in hemodialysis patients between 2012 and 2017 in an East-European Country: a retrospective study

Abstract: Purpose The aim of this study was to evidence trends and changes in mortality, comorbid conditions, prognosis, and causes of death after 5 years of continuous evolution of hemodialysis (HD) patients in Romania. Methods We included two cohorts of stable HD patients (901 from 2012 and 1396 from 2017). Both cohorts were followed up for 1 year. The 5-year survivors of the 2012 cohort were identified in 2017 and their data changes were assessed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
4
2
1
Order By: Relevance
“…A notable proportion of HD patients contend with comorbidities, encompassing conditions such as hypertension, cardiovascular events, and diabetes. 38,39 In our study cohort, a higher prevalence of these concurrent health issues was observed in patients with Kt/V<1.4 compared to the group achieving the Kt/V target. This observation emphasizes that our study cohort is not an exception and higher comorbidity burdens were evident in patients with suboptimal dialysis doses.…”
Section: Discussionmentioning
confidence: 50%
“…A notable proportion of HD patients contend with comorbidities, encompassing conditions such as hypertension, cardiovascular events, and diabetes. 38,39 In our study cohort, a higher prevalence of these concurrent health issues was observed in patients with Kt/V<1.4 compared to the group achieving the Kt/V target. This observation emphasizes that our study cohort is not an exception and higher comorbidity burdens were evident in patients with suboptimal dialysis doses.…”
Section: Discussionmentioning
confidence: 50%
“…The incidence of stroke was 22.22%, comparable to previous studies, reporting 25% [ 12 ]. In 2020, according to a study conducted by Chisavu et al, the mortality rate caused by cardiovascular diseases was reported as predominant, accounting for 53% of all cases [ 36 ]. Moreover, the primary cause of initiating hemodialysis among patients with a PINI over 1 is diabetic nephropathy (11 patients), which is also recognized as the predominant etiology of chronic kidney disease globally.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is advisable to continue investigating predictors of CV event risk in HD patients at different time stages to improve individualized prevention and treatment. Several studies 34,35 have highlighted that the epidemiological characteristics of HD patients who experience early CV events differ from those who experience such events at a later stage.…”
Section: Analysis and Discussion Of Predictors Of CV Event Risk Occur...mentioning
confidence: 99%